Mesothelioma - Diagnostics, Treatment and Basic Research 2022
DOI: 10.5772/intechopen.103669
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Pathogenesis of Malignant Mesothelioma

Abstract: Malignant mesothelioma (MM) is a malignancy that arises from the mesothelium, a thin layer of tissue that covers the body’s serous cavities, such as the pleural, peritoneal, pericardial, and tunica vaginalis of the testis. More than 80% of all mesothelioma cases originate from the pleura and approximately 75–80% of patients are males. It is almost always fatal with most of those affected dying within a year of diagnosis. Asbestos exposure is the most common cause of MM, which mostly affects the pleura. Various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 110 publications
2
4
0
Order By: Relevance
“…According to our study, mesothelioma typically affects adults within the age group of 60 and 79. This finding is supported by other studies and is compatible with the lengthy latent period of the disease [31,47]. Mazureck et al suggested that the majority of MM deaths, between 1999 and 2015 in the USA, occurred in both sexes between the ages of 75 and 84 [48].…”
Section: Discussionsupporting
confidence: 73%
“…According to our study, mesothelioma typically affects adults within the age group of 60 and 79. This finding is supported by other studies and is compatible with the lengthy latent period of the disease [31,47]. Mazureck et al suggested that the majority of MM deaths, between 1999 and 2015 in the USA, occurred in both sexes between the ages of 75 and 84 [48].…”
Section: Discussionsupporting
confidence: 73%
“…Mesothelioma arises when asbestos fibres enter the pleural or abdominal cavity, causing phagocytosis by macrophages. This can lead to an inflammatory reaction, followed by an increased risk of malignant transformation of mesothelial cells [ 80 ]. This risk is higher when the asbestos fibres are longer than 10 µm because of more difficult clearance by macrophages and thus failed attempts of phagocytosis [ 81 ].…”
Section: Mesotheliomamentioning
confidence: 99%
“…Furthermore, mesothelial cells exposed to asbestos fibres release inflammatory cytokines such as transforming growth factor (TGF) and vascular endothelial growth factor (VEGF), which generate an ideal environment for tumour growth. These factors are responsible for the increased risk and eventually the development of mesothelioma [ 80 ].…”
Section: Mesotheliomamentioning
confidence: 99%
“…The pleural location has a particularly high relationship with asbestos exposure (3,4). Despite widespread asbestos use bans, mesothelioma incidence is continuously rising (5). Nonetheless, despite bans, asbestos can continue to be present in some structures, such as schools or public buildings, and the construction of residential areas near previous asbestos mines, factories, or soil containing natural asbestos may still expose people to it(6, 7).…”
Section: Trial Registrationmentioning
confidence: 99%
“…Greece banned all forms of asbestos in 2005; production of asbestos reached its peak in 1996 and stopped in 1999 (20). Taking into consideration the long latency period of mesothelioma (which is referred to as 20-50 years), the increased mortality rate of this disease is expected during the early decades of the 21st century (5).…”
Section: Trial Registrationmentioning
confidence: 99%